2018
DOI: 10.3390/genes9110540
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and Genomic Approaches for Unravelling Candida albicans Biofilm Formation and Drug Resistance—An Update

Abstract: Candida albicans is an opportunistic fungal pathogen, which causes a plethora of superficial, as well as invasive, infections in humans. The ability of this fungus in switching from commensalism to active infection is attributed to its many virulence traits. Biofilm formation is a key process, which allows the fungus to adhere to and proliferate on medically implanted devices as well as host tissue and cause serious life-threatening infections. Biofilms are complex communities of filamentous and yeast cells su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 107 publications
0
27
0
Order By: Relevance
“…In addition to the Als family, other adhesins are important in mediating the initial attachment of C. albicans yeast cells during biofilm formation (Figure 1(A)). The enhanced adhesion to polystyrene protein (Eap1p) is significant in the clinical setting due to its ability to mediate attachment of C. albicans to plastics found in medical devices (Chong et al 2018;McCall et al 2019). Deletion of EAP1 renders C. albicans unable to attach to plastic surfaces and epithelial cells in vitro.…”
Section: Biofilm Formationmentioning
confidence: 99%
“…In addition to the Als family, other adhesins are important in mediating the initial attachment of C. albicans yeast cells during biofilm formation (Figure 1(A)). The enhanced adhesion to polystyrene protein (Eap1p) is significant in the clinical setting due to its ability to mediate attachment of C. albicans to plastics found in medical devices (Chong et al 2018;McCall et al 2019). Deletion of EAP1 renders C. albicans unable to attach to plastic surfaces and epithelial cells in vitro.…”
Section: Biofilm Formationmentioning
confidence: 99%
“…Biofilms are organized communities of cells developed after adhesion to a surface and enclosed in an ECM [107, 108]. The ability to grow as biofilms presents an advantage for fungal pathogens, regarding colonization and persistence in different host tissues [109], but also in the resilience against antifungal treatments [110, 111].…”
Section: Candida Evolution Towards Increased Biofilm Formationmentioning
confidence: 99%
“…With the development of genomics and the advent of whole genome sequencing platforms, metabolic pathways and related genes involved in fungal pathogenesis have been revealed ( Chong et al, 2018 ). The current study found that the anti-adhesive effects of SNH are more significant than its anti-biofilm effects, and to verify that SNH may inhibit biofilm formation by inhibiting initial adhesion, we sequenced the transcriptome of C. albicans at an initial adhesion phase in 256 μg/mL (1 MIC 80 ) SNH treatment and control groups through a high-throughput RNA sequencing method.…”
Section: Discussionmentioning
confidence: 99%